Rituals of Containment: Many Pandemics, Body Politics, and Social Dramas During COVID-19 in Pakistan - Ali, Inayat (Frontiers in Sociology, 2021)
Infecting millions of people, causing around two million deaths, and affecting billions of people worldwide during January 2021, the coronavirus 2019 (COVID-19) pandemic is not merely one pandemic but many. These many pandemics, which I identify herein, have revealed the overt and subtle entanglements among religion, science, and politics around COVID-19. Building on my current ethnographic research on COVID-19 using purposive sampling and interview guide in Pakistan, and borrowing from various anthropological concepts such as “social drama,” proposed by Victor Turner, and ritual, I have developed a concept that I call rituals of containment. With this concept, I extend my previous argument regarding “symbolic ownership” to show a visible “body politics” by demonstrating how religion, science, and politics around COVID-19 are entangled at individual and government levels. This has become observable through the rituals of the Pakistani government of containment to deal with COVID-19. Such entanglements are visible in the case of strategies to tackle infected “viral bodies,” as the government has enacted its authority: (1) to bury what I am terming the dead viral body without its beloved ones present; (2) to return or not to return this body to family members in a coffin; (3) or to provide the grieving family with a symbolic empty coffin. These Covidian politics have led to the question: Who in actuality owns the body? In conclusion, I argue that the problem lies in the discriminatory and contradictory rituals of containment of the government, not in using scientific evidence and guidelines.